The poetry of John Tyndall - Jackson, Roland; Jackson, Nicola; Brown, Daniel (Comparative literature and culture., 2020)
The Poetry of John Tyndall contains the 76 extant poems of leading scientist and philosopher, John Tyndall c.1822-1893). The poems are complemented by an extended introduction that addresses the relationship between science and poetry.